AcMNPV Core Gene ac109 Is Required for Budded Virion Transport to the Nucleus and for Occlusion of Viral Progeny - Alfonso, Victoria (2012)
The Autographa californica multiple nucleopolyhedrovirus (AcMNPV) ac109 core gene has been previously characterized as an essential late gene. Our results showed that budded virions could be detected in supernatants of infected Sf-9 cells, even when ac109 knockout viruses displayed a single-cell infection phenotype. Moreover, confocal microscopy analysis revealed that budded virions can enter the cytoplasm but are unable to enter the cell nucleus. This defect could be repaired by complementing ac109 in trans. In addition, polyhedra of normal size could be detected in Sf-9 nuclei infected with ac109 knockout viruses. However, electron microscopy demonstrated that these occlusion bodies were empty. Altogether, these results indicate that ac109 is required for infectivity of both phenotypes of virus.